Non-AIDS defining cancer (NADC) among HIV-infected patients at an oncology tertiary-care center in Mexico - Cornejo-Juárez, P. (AIDS Res Ther, 2018)
BACKGROUND: Non-AIDS defining cancers (NADCs) have been an increasing cause of morbidity and mortality in patients with HIV. There is no data on the spectrum of NADCs in Mexico. We describe the type of neoplasms, clinical characteristics, and outcomes of HIV-infected patients with NADCs. METHODS: We conducted a retrospective study of all patients with confirmed diagnosis of NADC attending the HIV/AIDS clinic at the National Cancer Institute in Mexico City (a tertiary-care center for adult patients with cancer) from January 1990 to December 2016. RESULTS: From 1126 HIV-positive individuals seen at the institute since 1990, 127 (11.3%) were diagnosed with NADCs; seven patients developed two NADCs during their follow-up. At diagnosis of NADC median age was 43.7 ± 10.9 years; 101 (79.5%) were male; median CD4 was 273 cells/mm(3), 70 patients had a CD4 count of > 200 cells/mm(3), 73 had undetectable HIV viral load and 82 had taken combined antiretroviral therapy (cART) for more than 1 year. The most frequent NADCs were in men, Hodgkin lymphoma (34.3%) followed by anal cancer (15.7%), whereas in women, were vulvo-vaginal cancers associated to human papilloma virus (HPV) (51.8%), followed by breast cancer (25.9%). The main risk factor associated with death was cancer progression or relapse (OR, 28.2, 2.5–317.1; p = 0.007). CONCLUSIONS: HL- and HPV-related neoplasms are the commonest NADC in a cancer referral hospital from a middle-income country with universal access to cART since year 2005. Screening for early anogenital lesions should be emphasized in patients with HIV. It is essential to establish multidisciplinary groups involving Hemato-oncologists, Oncologists, Gynecologists, and HIV Specialists in the treatment of these patients.